Award of the Arbitral Tribunal ([Permanent Court of Arbitration] The HagueNL, 2007)
Details the arguments of the parties and their submissions. Outlines the delimitation of the territorial sea and the continential shelf in the Exclusive Economic Zone. Presents the Tribunal's findings in the case.
Keywords: BOUNDARIES